A Subset of Colorectal Cancers with Cross-Sensitivity to Olaparib and Oxaliplatin - Arena, Sabrina; Corti, Giorgio; Durinikova, Erika; Montone, Monica; Reilly, Nicole M; Russo, Mariangela; Lorenzato, Annalisa; Arcella, Pamela; Lazzari, Luca; Rospo, Giuseppe; Pagani, Massimiliano; Cancelliere, Carlotta; et al. (Clinical cancer research, 2020)
Defects in the homologous recombination (HR) repair pathway are of clinical interest due to sensitivity of HR-deficient cells to PARP inhibitors. We were interested in defining PARP vulnerability in patients with metastatic colorectal cancer (mCRC) carrying and mutations who display poor prognosis, have limited therapeutic options, and represent an unmet clinical need. We tested colorectal cancer cell lines, patient-derived organoids (PDO), and patient-derived xenografts (PDX) enriched for and mutations for sensitivity to the PARP inhibitor olaparib, and the chemotherapeutic agents oxaliplatin and 5-fluorouracil (5-FU). Genomic profiles and DNA repair proficiency of colorectal cancer models were compared with pharmacologic response. Thirteen of 99 (around 13%) colorectal cancer cell lines were highly sensitive to clinically active concentrations of olaparib and displayed functional deficiency in HR. Response to PARP blockade was positively correlated with sensitivity to oxaliplatin in colorectal cancer cell lines as well as patient-derived organoids. Treatment of PDXs with olaparib impaired tumor growth and maintenance therapy with PARP blockade after initial oxaliplatin response delayed disease progression in mice. These results indicate that a colorectal cancer subset characterized by poor prognosis and limited therapeutic options is vulnerable to PARP inhibition and suggest that PDO-based drug-screening assays can be used to identify patients with colorectal cancer likely to benefit from olaparib. As patients with mCRC almost invariably receive therapies based on oxaliplatin, "maintenance" treatment with PARP inhibitors warrants further clinical investigation.